ENGLISH AS A FOREIGN LANGUAGE AND ENGLISH LEARNING IN INDONESIA’S HIGHER EDUCATION SETTING : LEARNING FROM HISTORICAL FACTS OF EFL LEARNING IN INDONESIA - Zainal ‘Arifin (2024)
Language learning is the manifestation of language policy. As English has been decided to be a foreign language not the second that potentially provide more opportunity for the language to occupy Indonesian socio-political, economic, and cultural aspect but has been regarded endanger their “preservation”, some considerations in English language planning in Indonesia especially in higher education need to be reviewed when English is also regarded as the most important language used in academic atmosphere. The claim of the existance of paradox between the language policy and the academic community’s demand toward English does not probably exist. There might be a missing link between the policy in the level of macro, meso, and micro. This article is intended to analize the status of English in Indonesia and investigate the fact of EFL in higher education in Indonesia to provide implication for future language education planning